OLEUROPEIN REDUCES CISPLATIN-INDUCED NEPHROTOXICITY IN HUMAN EMBRYONIC RENAL EPITHELIAL “GP-293” CELLS - Maryam Rezaei (Herbal Medicines Journal, 2016)
Background and Aim:The protective effect of oleuropein,a chief polyphenol compound in olive tree, on cisplatin-induced nephrotoxicity in human cultured renal tubular cells, GP-293, was investigated.